Karsinoma Sel Basal pada Petani Karet Tradisional - Sumirat, Ratih Nurdiany; Soemarko, Dewi; Harahap, Sabasdin (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Basal cell carcinoma (BC) is a malignant neoplasm of non-katinized cells in the basal layer of the epidermis, is locally invasive, aggressive, destructive, and rarely metastasizes. KSB is more common in the elderly. The etiopathogenesis associated with KSB is genetic, environmental, and most commonly ultraviolet light exposure. Clinically, there are five types of SCI, namely nodular, superficial, morpheaform, pigmented, and Pinkus fibroepithelioma. Early detection of skin cancer can be done by skin self-examination (SAKURI). The purpose of this study was to determine clinical signs as predictors of basal cell carcinoma in traditional rubber farmers. Through 7 steps of occupational diagnosis, it can be concluded that the diagnosis of Basal Cell Carcinoma in patients is related to their work as traditional rubber farmers. Appropriate definitive and non-medicamentous management and patient compliance can restore the patient's health condition with a good prognosis.